Vaccine hesitancy and the resurgence of vaccine preventable diseases: the way forward for Malaysia, a Southeast Asian country - L. P. Wong; P. F. Wong; S. AbuBakar (Human Vaccines & Immunotherapeutics, 2020)
This study engaged health professionals in in-depth, semi-structured interviews to explore their opinions concerning the issues surrounding vaccine hesitancy in Malaysia and strategies to improve vaccination to stamp the rise of vaccine preventable diseases (VPDs). Opinions on how to address the resurgence of VPDs in the era of increasing vaccine hesitancy were obtained. Eight health professionals, including geriatricians, pediatricians, microbiologists, public health specialists, and family medicine specialists were interviewed. The influence of anti-vaccination propaganda, past-experience of adverse event following immunization (AEFI), perceived religious prohibition, a belief that traditional complementary and alternative medicine (TCAM) use is safer, pseudoscience beliefs, and anti-vaccine conspiracy theories were identified as reasons for refusing to vaccinate. The interplay of social, cultural and religious perspectives in influencing perceived religious prohibition, pseudoscience beliefs, and the use of TCAM contributing to vaccine refusal was found. Five broad themes emerged from the health professionals regarding strategies to address vaccine hesitancy, including establishing an electronic vaccination registry, increasing public awareness initiatives, providing feedback to the public on the findings of AEFI, training of front-line healthcare providers, and banning the dissemination of anti-vaccine information via social media. With regards to identifying strategies to address the resurgence of VPDs, mandatory vaccination received mixed opinions; many viewed supplementary immunization activity and the prevention of travel and migration of unvaccinated individuals as being necessary. In conclusion, the present study identified unique local cultural, traditional and religious beliefs that could contribute to vaccine hesitancy in addition to issues surrounding vaccination refusal similarly faced by other countries around the world. This information are important for the formulation of targeted intervention strategies to stamp vaccine hesitancy in Malaysia which are also a useful guide for other countries especially in the Southeast Asia region facing similar vaccine hesitancy issues.